Consultations on driving in people with cognitive impairment in primary care: A scoping review of the evidence. - Carol Sinnott; Tony Foley; Justin Forsyth; Kathleen McLoughlin; Linda Horgan; Colin P Bradley (PLoS ONE)
Objectives To review the empirical evidence on approaches used by Primary Care Physicians (PCPs) in fitness to drive (FtD) consultations with people living with cognitive impairment. Design Scoping review of empirical literature focused on primary studies of any design. Setting Primary care practice. Participants PCPs or their equivalent and/ or individuals with cognitive impairment across the spectrum of mild cognitive impairment to dementia. Measurements Systematic search of Medline, Cinahl, PsychINFO, Academic Search Complete, Psychological and Behavioural Sciences Collection, SocIndex and Social Sciences FT were conducted. Records screened by two reviewers against agreed inclusion criteria. Mixed studies (qualitative and quantitative) were synthesized within overarching themes. Results Eighteen studies met our inclusion criteria. Synthesized data showed PCPs have mixed feelings on the appropriateness of their role in FtD assessments, with many feeling particularly uncomfortable and lacking confidence in the context of possible cognitive impairment. Reasons include lack of familiarity with legal requirements and local resources; fear of damaging the doctor-patient relationship; and impact on the patient's quality of life. Patients voiced their desire to maintain agency in planning their driving cessation. Studies evaluating pragmatic educational programmes suggest these can improve physician confidence in FtD consultations. Conclusion The increasing number of older people affected by cognitive impairment, for whom driving may be a concern, has implications for primary care practice. Addressing the reasons for PCPs lack of comfort in dealing with this issue is essential in order for them to better engage in, collaborative discussion with patients on plans and preferences for driving cessation.